Technology Integration Models and Frameworks in Teaching and Training - Bajracharya, Jiwak Raj (Journal of Training and Development, 2021)
The purpose of this study is to review the existing models and frameworks which has been implemented for technology integration during teaching and training. As discussed in the numerous literature Technological Pedagogical and Content Knowledge (TPACK), Substitution, Augmentation, Modification, Redefinition (SMAR), TPACK-based ID models such as TPACK-Comprehension, Observation of instruction, Practice of instruction, and Reflection on TPACK (TPACK-COPR) model, Introduce-TPACK, Demonstrate, Develop, Implement, Revise - a TPACK-based lesson, and Reflect on a TPACK-based lesson (TPACK-IDDIRR1) model, and TPACK-IDDIRR2 model have been applied by today’s instructors and trainers to achieve the specific goal for effective teaching and training. This paper intends to highlight the key features of the above-mentioned models and frameworks with few hurdles as found in the empirical-based studies. It also discusses how those hurdles could be mitigated by addressing the extraneous cognitive load of instructors as well as trainers to carry out technology integration with future recommendations for the research. It was found that specific frameworks and models are limited to the macro-level concept but today’s instructors, as well as trainers, are required to have adequate instructional guidance in chronological steps so that they could implement those models and frameworks in their teaching and training for productive outcomes.